Comparison of the “Late Catch-Up” Phenomenon Between BuMA Supreme and XIENCE Stents Through Serial Optical Coherence Tomography at 1–2 Month and 2 Year Follow-Ups: A Multicenter Study - Qinhua Jin; Jianguo Cui; Changqian Wang; Bei Shi; Xi Su; Guosheng Fu; Yanqing Wu; Qiansu Yang; Yundai Chen (Cardiovascular Innovations and Applications)
Objectives: This study was aimed at comparing the “late catch-up” phenomenon between the BuMA Supreme bioresorbable polymer sirolimus-eluting stent and the XIENCE stent through serial optical coherence tomography (OCT) at within 2 months and 2 year follow-ups. Methods: A total of 49 of 75 patients from the PIONEER-II study were enrolled in a 2 year OCT follow-up study; 44 patients with 50 lesions were included in the statistical analysis. The primary endpoints were neointimal thickness and late luminal loss (LLL) after stent implantation. Results: The stenosis diameter, and minimum in-stent or in-segment diameter, did not significantly differ between the BuMA Supreme and XIENCE arms at within 2 months and 2 year follow-ups. The strut neointimal coverage and thickness were greater in the BuMA group than the XIENCE group at the 1 and 2 month follow-ups (P = 0.044 and P = 0.010, respectively) but not at the 2 year OCT follow-up. Neither early luminal loss at the within 2 months follow-up (P = 0.849) nor LLL at the 2 year OCT follow-up (P = 0.613) showed differences between device arms. No significant differences in imaging and clinical endpoints were observed between device arms at follow-up. Conclusions: The BuMA Supreme stent’s faster re-endothelization with no “late catch-up” phenomenon has potential advantages over the XIECE stent for patients with coronary artery disease and high bleeding risk because it decreases the duration of dual antiplatelet therapy.